Desenvolvimento de atemoieiras em diferentes sistemas de plantio e sensibilidade a herbicidas - Silveira, Gustavo Cesar Dias (2022)
The present work has the objective of evaluating implantation techniques of atemoya orchards, in different types of soils, that better provide a good establishment and production and also the selectivity on atemoya rootstock seedlings to herbicides, in order to increase the control of weeds. First, an experiment was installed in 2 types types of soil, argisol and latosol experiments, with design in random composite blocks (DBC), 5 treatments, 5 repetitions and 6 made up each plot. Treatment 5 (plowing+harrowing+furrower+pit beater+additional limestone) had the best performance in average productivity in both soil types. The work refers to the evaluation of the sensitivity of seedlings of araticum-de-terra- fria, rootstock of atemoya, to the phytotoxic effects of post-emergence herbicide application. The experimental design used was randomized blocks of 4 years and 8 treatments, experimental plot was for three seedlings of approximately 1 m in height. Phytotoxicity estimates and comparison of chlorophylls a, b and total and visual a/b were performed. The herbicides Fomesafem, Cletodim, Carfentrazone-ethyl, Imazetapir, showed more promising results because they do not cause severe damage like araticum seedlings.